2021
DOI: 10.7196/samj.2021.v111i8.15766
|View full text |Cite
|
Sign up to set email alerts
|

Low 30-day mortality in South African orthopaedic patients undergoing surgery at an academic hospital during the first wave of the COVID-19 pandemic: It was safe to perform orthopaedic procedures at our hospital during the first COVID-19 peak

Abstract: South Africa (SA) remains in a national state of disaster due to COVID-19 and the ongoing detection of active SARS-CoV-2 cases in our population, mainly driven by the local Beta variant 501Y.V2. Our nation's recorded recovery rate remains high at 92%. [1] Groote Schuur Hospital (GSH), one of the two state academic hospitals in our area, services patients from vulnerable communities, where infectious diseases such as tuberculosis and HIV continue to dominate the health landscape and multiple comorbidities exist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…After surgery, 93 fatalities were documented, 49 of which happened within a day following operation 7 . In August 2021, Waters et al 8 reported a 2.5% death rate after orthopedic procedures in 346 patients in South Africa. According to Paterson and colleagues, women in Africa are at a greater risk of suffering postoperative problems and dying.…”
Section: The Pom Burden In Africamentioning
confidence: 99%
“…After surgery, 93 fatalities were documented, 49 of which happened within a day following operation 7 . In August 2021, Waters et al 8 reported a 2.5% death rate after orthopedic procedures in 346 patients in South Africa. According to Paterson and colleagues, women in Africa are at a greater risk of suffering postoperative problems and dying.…”
Section: The Pom Burden In Africamentioning
confidence: 99%